Social and ethnic integration through shaping cultural landscape in urban residential areas towards achieving One-Malaysia concept - Aziz, Nurul 'Aqilah (2014)
The cultural landscape is a reflection and evidence of human responses to the environment, including the elements of imaginative and spiritual vitality embedded in their way of life. In a modern residential setting, the cultural landscape plays the role of representing an impression of the natural environment, a green component for people in the form of serenity, calmness, aesthetics, edible products and meaningful values in addition to giving natural resources for health. The majority of residential areas in Malaysia are populated by three major ethnicities, namely the Malay, Chinese and Indian communities. The literature shows evidence of cultural landscapes to encourage socially and environmentally harmonious living environments. This potential to address the various issues and gaps between ethnic groups in local neighbourhoods that lead to integration, which however still not being fully explored in Malaysia. At the same time, the contributions of a cultural landscape in an urban residential area are not well-established. These green areas are perceived as having designs that are behind the times, outdated, old-fashioned and not relevant in a modern technological world as one of the ways to enhance the physical character of the residential area. On the other hand, evidence from various studies also indicate the contrasting theory on cultural landscape which highlights this type of garden as promising to be one of the ways to elevate social and ethnic integration in semi-private gardens in urban residential areas. This qualitative research is adopted with case study in medium-cost housing in Saujana Puchong, Selangor. A pilot study was conducted which is Focus Group Discussion (FGD) among professionals in order to capture their review and strengthen the issues of this research. Semi-structured interviews were conducted in order to discover the landscape characteristics of medium-cost housing to foster ethnic integration. The findings of this research provide the evidence that there are ethnic influences residential landscape characteristics which refer to cultural landscape. These cultural landscapes embedded with high values and potential to be used as elements to bridge important national issues pertaining to ethnic integration, while at the same time stimulating the feeling of neighbourliness and caring for the environment. Due to the limited open spaces provided for each unit houses, this research provides the design for multi-ethnic community garden that can be implemented in urban residential areas.